Psychological and neuropsychological effects of MDMA use during adolescence: a structured review - Miazzi, Rocco; Cestonaro, Clara; Righetto, Silvia; Petroni, Giulia; Terranova, Claudio (Frontiers in Psychiatry, 2025)
This structured review critically examines the psychological and neuropsychological effects of MDMA (3,4-methylenedioxymethamphetamine) use during adolescence, focusing exclusively on human studies. MDMA is a widely consumed psychoactive substance among adolescents, particularly in social and recreational contexts. Drawing on 14 eligible studies identified through a comprehensive literature search in MEDLINE/PubMed and through reference screening, this review synthesizes evidence concerning MDMA’s impact on adolescent mental health and cognitive function. The findings reveal consistent associations between adolescent MDMA use and a range of psychological disturbances, including increased depressive and anxious symptoms, as well as more severe manifestations such as suicidal ideation and attempts. Neuropsychological impairments are also commonly reported, with deficits in memory, attention, and executive functioning linked to early exposure. Neuroimaging evidence indicates that MDMA disrupts serotonergic pathways, potentially leading to persistent alterations in brain function. Although the evidence suggests significant risks, the review highlights several methodological limitations in the current literature, including small sample sizes, high rates of polydrug use, and the lack of longitudinal designs. These factors complicate causal interpretations and underscore the need for further, more robust research. The review emphasizes the urgency of targeted prevention strategies and harm reduction efforts aimed at adolescents. Understanding the specific vulnerabilities of the adolescent brain to MDMA’s neuropsychological effects is essential for clinicians, educators, and policymakers. Overall, this review provides a focused and human-centered perspective on the psychological and neuropsychic consequences of MDMA use in adolescence, reinforcing the call for greater public health awareness and scientific investigation.